Penambahan Konsentrat dan Jamu Ternak Terhadap Pertumbuhan Sapi Bali Dara Pra Sapih - Siska Fitriyanti; Askalani Askalani; Surya Nur Rahmatullah (www.ulm.ac.id, 2015)
The research was conducted in the Institute for Assessment and Development ofIntegrated Farming (BP3T) in Tambang Ulang. The aim of research was to study the use ofsupplemental feed (concentrate) based on corn by product in increasing the performance Baliheifer. Fourteen Bali heifer were divided into two groups, those were group A (feeding forage,concentrate, and cattle herbs) and group B (feeding forage and concentrate). The averagesweight gain during the 81 days were 0.49 and 0.27 kg/head/day respectively for treatments A andB, while feed consumption and feed conversion of each treatment were 19.29 kg/head/day and8.36 for A and 19.29 kg/head/day and 16.04 for B, respectively. In conclusion, herb cattlesupplementation could increase Bali heifer weight gain better than fed concentrate only